Lesbian health : current assessment and directions for the future - Solarz, Andrea L.; Institute of Medicine (U.S.). Committee on Lesbian Health Research Priorities (Washington, D.C. : National Academy Press, 1999)
Women's health, as a field of study, is a developing discipline. Health theories in general have been based on studies of men. However, in recent years, more attention has shifted to women's health, realizing the disparities between men and women in relation to their health. During the last two decades, a similar shift has occurred for a group of women -- lesbian women -- to further identify and specify their health needs.
Over the past decade, lesbians have organized to call for attention to the health issues of this community, resulting in several federally funded research initiatives. This book offers a comprehensive view of what is known about lesbian health needs and what questions need further investigation, including: -- How do we define who is lesbian?-- Are there unique health issues for lesbians?-- Are lesbians at higher or lower risk for such health problems as AIDS, sexually transmitted diseases, breast cancer, mental disorders, and substance abuse?-- How does homophobia affect lesbian health and the funding of research on lesbian health?-- How do lesbian health needs fit into the health care system and the larger society?-- What risk and protective factors shape the physical and mental health of lesbians?
The book discusses how to determine which questions to ask about sexual orientation, the need to obtain information without violating privacy, the importance of considering racial and ethnic diversity in the study of lesbians, strategies for exchanging information among researchers and disseminating findings to the public, and mechanisms for supporting greater numbers of researchers.
1. Introduction -- 2. Lesbian Health Status and Health Risks -- 3. Methodological Challenges in Conducting Research on Lesbian Health -- 4. Contextual Barriers to Conducting Research on Lesbian Health -- 5. Conclusions and Recommendations -- App. A. Selected Bibliography on Lesbian Health Research.
Report based on a workshop held in Oct. 1997.
"Selected Bibliography on Lesbian Health Research": pages 165-206.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: Lesbians -- Health and hygiene; Lesbians -- Health and hygiene -- Government policy -- United States; Women -- Health and hygiene; Lesbianism; Homosexuality, Female; Women's Health; United States; Lesbiennes -- Santé et hygiène.; Lesbiennes -- Santé et hygiène -- Politique gouvernementale -- États-Unis.; Femmes -- Santé et hygiène.; Lesbianisme; MEDICAL -- Preventive Medicine; HEALTH & FITNESS -- Healthy Living; HEALTH & FITNESS -- Reference; HEALTH & FITNESS -- Holism; Women -- Health and hygiene; Lesbians -- Health and hygiene; United States; Homosexualité féminine -- États Unis d'Amérique.; Santé publique -- États Unis d'Amérique.; Santé des femmes -- États Unis d'Amérique.